2006
DOI: 10.1016/j.margeo.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Cenozoic sedimentation along the continental rise of the Bellingshausen Sea, West Antarctica

Abstract: Seismic reflection profiles, bathymetric and magnetic data collected along and across the continental margin of the Bellingshausen Sea provide new constraints and interpretations of the oceanic basement structure and Cenozoic glacial history of West Antarctica. Evidence for tectonic boundaries that lie perpendicular to the margin has been identified on the basis of one previously unpublished along-slope multichannel seismic reflection profile. By combining several magnetic data sets, we determined basement age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
2
44
0
1
Order By: Relevance
“…The seismic profiles revealed unconformities on the outer shelf and evidence for debris flows and slumps on the slope. These depositional patterns were interpreted as results of repeated WAIS advances and retreats across the shelf during the Pliocene and Quaternary (Nitsche et al, 1997(Nitsche et al, , 2000Cunningham et al, 2002;Scheuer et al, 2006). Nitsche et al (1997Nitsche et al ( , 2000 noted that the slope in the study area is gentler (1e2 ) but that the shelf break prograded further (w32 km) than in other areas of the Bellingshausen and Amundsen seas.…”
Section: Previous Workmentioning
confidence: 91%
See 1 more Smart Citation
“…The seismic profiles revealed unconformities on the outer shelf and evidence for debris flows and slumps on the slope. These depositional patterns were interpreted as results of repeated WAIS advances and retreats across the shelf during the Pliocene and Quaternary (Nitsche et al, 1997(Nitsche et al, , 2000Cunningham et al, 2002;Scheuer et al, 2006). Nitsche et al (1997Nitsche et al ( , 2000 noted that the slope in the study area is gentler (1e2 ) but that the shelf break prograded further (w32 km) than in other areas of the Bellingshausen and Amundsen seas.…”
Section: Previous Workmentioning
confidence: 91%
“…The first marine geoscientific data published from the southern Bellingshausen Sea were multi-channel seismic profiles crossing the outer shelf, continental slope and rise (Nitsche et al, 1997(Nitsche et al, , 2000Cunningham et al, 2002;Scheuer et al, 2006). The seismic stratigraphy on the outer shelf and slope shows a general transition from aggradational to progradational and then back to aggradational geometries.…”
Section: Previous Workmentioning
confidence: 99%
“…3) is located closest to the continental margin. It crosses one of the largest sediment mounds (about 130 km wide and 700 m high) of the West Antarctic continental margin, referred to as Depocentre C by Scheuer et al (2006). This mound developed on the elevated basement at the eastern side of the tectonic boundary defined by the BGA.…”
Section: Profile Bas-92324mentioning
confidence: 99%
“…Channel-related contourite drifts and individual sediment mounds have been observed along the Antarctic Peninsula margin (e.g. Rebesco et al 1997) whereas a wide trough-mouth fan has been identified along the continental margin in the central Bellingshausen Sea (Scheuer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The age for the oldest ridge-trench collision in the western Bellingshausen Sea can be roughly estimated to be about 50 Ma, using a few identified spreading anomalies (Eagles et al, 2004;Scheuer et al, 2006). Oceanic crustal age along the margin becomes progressively younger toward the northeast (Larter and Barker, 1991).…”
Section: Subduction To Ridge Collisions: the Converted Active-to-passmentioning
confidence: 99%